Development plan for the library of the Isabela School for the Deaf - Pascual, Charlito C. Jr (School of Library and Information Studies, University of the Philippines Diliman, 2017)
This study was conducted to help the deaf students of the Isabela School for the Deaf, one of the major Deaf schools in the region, in utilizing the library.